Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.neuroscience.2014.06.037
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy in superficial spinal dorsal horn accelerates the cathepsin B-dependent morphine antinociceptive tolerance

Abstract: Opioids are the most widely used analgesics in the treatment of severe acute and chronic pain. However, opioids have many adverse side effects, including the development of antinociceptive tolerance after long-term use. The antinociceptive tolerance of opioids has limited their clinical use. A recent study has reported that autophagy is responsible for morphine-induced neuronal injury. However, little is known about the role of autophagy in morphine antinociceptive tolerance. In the present study, chronic morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 53 publications
1
20
1
Order By: Relevance
“…A previous study found that chronic morphine administration induced autophagy in GABAergic interneurons from the spinal cord; 18 however, we did not observe autophagy in the midbrain GABAergic interneurons in this study. The apparent discrepancy might be caused by several factors that are crucial for drug-induced plasticity, such as the age of the mice (8-wkold C57BL/6 male mice in our experiments versus 10-wk-old in ref.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…A previous study found that chronic morphine administration induced autophagy in GABAergic interneurons from the spinal cord; 18 however, we did not observe autophagy in the midbrain GABAergic interneurons in this study. The apparent discrepancy might be caused by several factors that are crucial for drug-induced plasticity, such as the age of the mice (8-wkold C57BL/6 male mice in our experiments versus 10-wk-old in ref.…”
Section: Discussioncontrasting
confidence: 99%
“…9,12 Autophagy is a lysosome-mediated degradation pathway actively involved in drug addiction. [17][18][19][20] It has been reported that autophagy regulates the axonal and dendritic degeneration of neurons. 21 Both ATG5 (autophagy-related 5) and ATG7 (autophagy-related 7) are required for the maintenance of axonal homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Kabeya et al, 2000). Recently, Beclin 1 has been known as an important autophagy marker and widely used in evaluating the activation of autophagy (Hayashi et al, 2014). In this study, LC3-II significantly increased and peaked at 8 and 72 h in the spinal cords of the I/R group (P < 0.05, Fig.…”
Section: Autophagy Was Upregulated After I/r Injurymentioning
confidence: 51%
“…Several recent studies with other psychostimulants suggest involvement of autophagy in neurotoxicity [30,33]. For example, morphine-mediated autophagy is responsible for the development of morphine antinociceptive tolerance [39] and methamphetamine has been reported to induce cell death via autophagy [40]. This study revealed for the first time that cocaine exposure induces autophagy in SVGA astrocytes through sigma 1 receptor and mTOR, and PI3KIII/Beclin-1 pathways are involved in cocaine-mediated autophagic process.…”
Section: Discussionmentioning
confidence: 99%